The free verse in José Lezama Lima's poetry. Three specific cases - Navarro Pérez, Franco (2021)
This article studies the elements that make up free verse in José Lezama Lima's poetry from the theoretical approach of modern versology. The hypothesis proposes that in his free verse there is a return to metric sources of antitquity, that is to say, the ancient verse, using the coupling and semantic rythmic groups. The work develops the structural analysis from the formal plane on three specific cases: “Muerte de Narciso”, “Rueda el cielo”, “Hai Kai en gerundio” and, finally, theconclusions.